Potential Resistance to Antineoplastic Aminated Fullerenes Mediated by M2-Like Monocyte-Derived Exosomes - Huo, Jiawei; Zhou, Wei; Liu, Yang; Yang, Sifen; Li, Jie; Wang, Chunru (Frontiers in Oncology, 2022)
Exosomes are small extracellular vesicles critical for intercellular signaling via their delivery of cargoes, including proteins, DNA, RNA, lipids, and metabolites. Exosomes play essential roles in remodeling the tumor microenvironment (TME) for tumor growth, metastasis, and drug resistance. Aminated fullerenes (e.g., C70-ethylenediamine [EDA]) exhibit antineoplastic effects by targeting multiple functional proteins. Nanosized C70-EDA with positive surface charges tends to be taken up by monocytes in the bloodstream and monocyte-derived macrophages in the TME. Herein, the alterations of monocytes and monocyte-derived exosomes by C70-EDA have been investigated. C70-EDA reprogramed THP-1 monocyte to an M2-like state and substantially increased the protein content in exosomes secreted by M2-like monocytes. Notably, C70-EDA-induced M2-like monocytes released exosomes that triggered the proliferation of recipient tumor cells, which may alleviate the antineoplastic efficacy of C70-EDA. As revealed by proteomic profiling of exosomes, this outcome is probably a result of Rho GTPase/p21-activated kinase (PAK) pathway activation in recipient tumor cells induced by upregulated exosomal proteins. This work indicates a promising strategy in which aminated fullerenes can be combined with PAK inhibitors for cancer therapy.